Mobile virtual reality for musical genre learning in primary education. (October 2019) - Innocenti, Edoardo Degli; Geronazzo, Michele; Vescovi, Diego; Nordahl, Rolf; Serafin, Stefania; Ludovico, Luca Andrea; Avanzini, Federico
Abstract: Mobile virtual reality (VR) is increasingly becoming popular and accessible to everyone that holds a smartphone. In particular, digital didactics can take advantage of natural interaction and immersion in virtual environments, starting from primary education. This paper investigates the problem of enhancing music learning in primary education through the use of mobile VR. To this end, technical and methodological frameworks were developed, and were tested with two classes in the last year of a primary school (10 years old children). The classes were involved in an evaluation study on music genre identification and learning with a multi-platform mobile application called VR4EDU. Students were immersed in music performances of different genres (e.g., classical, country, jazz, and swing), navigating inside several musical rooms. The evaluation of the didactic protocol shows a statistically significant improvement in learning genre characterization (i.e., typical instruments and their spatial arrangements on stage) compared to traditional lessons with printed materials and passive listening. These results show that the use of mobile VR technologies in synergy with traditional teaching methodologies can improve the music learning experience in primary education, in terms of active listening, attention, and time. The inclusion of pupils with certified special needs strengthened our results.